Respuesta :

pegah
if you want to factor this question you should only factor x^-x-6 so you will have:
x^2 -x -6 = (x-3)(x+2) 
so now you have:
2x(x-3)(x+2) and that is the answer :))))
i hope this is helpful
have a nice day 
ok so you can leave the 2x out since that is already a factor

form is normally
ax^2+bx+c
a=first term
b=second term
c=third term
so now we look at the first terms
it is 1
good
now we look at the value of the middle and lastt term
second term=-1
third term=-6
we need to find what 2 factors of -6 add to -1
-6=-3 times 2
-3+2=-1
(x-3)(x+2)

so the factored form is
(2x)(x-3)(x+2)